Optimizing PAMSIMAS management: community-based training to enhance knowledge and skills of Village Officials in Banjar Regency - Husnul Khatimah; Fakhrurrazy Fakhrurrazy; M Zakiyuddin; Afif Fakhri (Universitas Muhammadiyah Magelang, 2024)
The Community-Based Drinking Water and Sanitation Provision Program (PAMSIMAS) serves as a community-driven platform for rural drinking water and sanitation development. In the Banjar Regency area, PAMSIMAS management faces challenges, including a limited number of available water reservoirs and a slow water-filling process into these reservoirs. Additionally, there is a shortage of qualified human resources for community training. To address these issues, activities were conducted to enhance community skills in maintaining PASMIMAS equipment. Collaboration took place with work units in the Banjar Regency government, involving 30 village officials in the West Martapura District. The method employed included lectures and question-and-answer sessions. The analysis utilized to evaluate the training's success involved pre-test and post-test assessments. The results indicated an increase in participants' knowledge, with a pre-test average of 40.66 and a post-test average of 70.50, yielding a p-value of > 0.00 (paired t-test). In conclusion, this training effectively enhanced PAMSIMAS knowledge among village officials.